A general strategy to achieve see-through devices through the micro-structuring of colored functional materials - Zishou Hu; Xueqing Tang; Yuan-Qiu-Qiang Yi; Shuhong Nie; Xiaolian Chen; Wenya Xu; Chenchao Huang; Xinju Mu; Zhongsheng Ma; Pengyu Tang; Xinzhou Wu; Wenming Su; et al. (Nature Communications)
Abstract Irrespective of the specific see-through device, obtaining optimal transparency remains the primary goal. In this work, we introduce a general strategy to enhance the transparency of various see-through devices. We achieve this by structuring the colored functional materials into imperceptible three-dimensional mesh lines, addressing a common challenge in multi-layer structures where each layer causes a reduction in transparency due to their color or opacity. To overcome this limitation, we selectively integrate functional materials into micron-wide groove structures transforming functional layers to functional meshes. Regardless of the initial color of the functional material, the resulting functional mesh can exhibit a high transmittance of 88% (vs. air) under any operating state while maintaining its intended function within the device. We apply this strategy to fabricate proof-of-concept of devices such as electrochromic devices, supercapacitors, and zinc batteries, all of which exhibit remarkable overall transparency when compared to the multi-layer device.